The evolution of Islamic venture capital in Malaysia: an expository study - Akunle Mikail, Sa'id; Arifin, Mahamad; Hassan, Rusni (LexisNexis Malaysia Sdn Bhd, 2013)
Islamic venture capital is a strategic tool to enhance cooperation in the Muslim world. This is because it helps form smart partnership among the members of OIC countries. Venture capital is an investment in highly risky projects in return for potential high return focusing mainly on technology. For more than a decade, the trend has shown tremendous changes; hence venture capital investment records increasing interest of the investors in other sectors such as agricultural production, medical instruments and others. Islamic venture capital has been running in parallel with the mainstream in Malaysia. There are several reasons supporting the emergence of Islamic venture capital namely, attraction of Middle East investors and underutilisation of surplus in the Muslim world. This paper traces the development of Islamic venture capital in Malaysia, identifies the regulatory bodies, and the policy initiatives, and the pioneer corporations. In conclusion, it examines three phases of the development of Islamic venture capital in Malaysia namely, the evolutionary process, the degree of incorporation and developmental patterns. The applied Shariah mechanisms are hybrid of musharakah, mudarabah, and wakalah. It suggests that the balance between supply side and demand side, public friendly regulation may actualise the Malaysian industrialisation dream. In addition, refocusing long-term investment, reorientation of SMEs towards venture capital investment, establishment of private-oriented venture capital industries, creation of cash waqf and/or Islamic social bank are some suggested solutions in promoting Islamic venture capital in Malaysia. They may also be of help to other jurisdictions. Key words: Islamic venture capital, Musharakah and Mudarabah, venture capital, supply and demand side, policy making and planning approach, problem-solving approach.